2015
DOI: 10.1111/vsu.12406
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Short‐Term Postoperative Analgesia by Epidural, Femoral Nerve Block, or Combination Femoral and Sciatic Nerve Block in Dogs Undergoing Tibial Plateau Leveling Osteotomy

Abstract: In dogs undergoing unilateral TPLO, bupivacaine administered via FNB, alone or in combination with sciatic nerve block, can provide short-term postoperative analgesia not different to that with administration via lumbosacral epidural.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 16 publications
0
13
0
Order By: Relevance
“…Regardless of the particular technique that is used, the nerve blocks can be used as either the principal anesthetic or, more commonly, as adjuncts to general anesthesia [ 1 4 , 9 , 17 , 20 , 21 ]. If a local anesthetic of sufficient duration is selected, nerve conduction blockade has the potential to provide substantial post-operative pain relief as well [ 1 3 , 17 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regardless of the particular technique that is used, the nerve blocks can be used as either the principal anesthetic or, more commonly, as adjuncts to general anesthesia [ 1 4 , 9 , 17 , 20 , 21 ]. If a local anesthetic of sufficient duration is selected, nerve conduction blockade has the potential to provide substantial post-operative pain relief as well [ 1 3 , 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Initial studies reported the anatomical considerations for blocking the two main nerves, the FN and the ScN, at different locations along their courses while subsequent studies described the volume of dye that is required to stain a desired length of target nerve in cadaver specimens and the technical aspects of using ultrasound and/or nerve stimulation to perform these peripheral nerve blocks [ 5 , 6 , 10 , 11 ]. Clinical studies have documented the effects of different FN and ScN blocks on intraoperative analgesia, recovery quality, and the incidence of side effects and complications related to their use for surgical procedures of the pelvic limb [ 1 , 2 , 3 , 4 , 9 , 17 , 20 , 21 ]. Based on these clinical studies in dogs, advantages of using PNBs over neuraxial or opioid-based methods of perioperative pain control include decreased inhaled anesthetic requirements, better maintenance of blood pressure during anesthesia, smoother recoveries from anesthesia, less post-operative urinary retention, and equivalent or superior postoperative analgesia.…”
Section: Introductionmentioning
confidence: 99%
“…Perineural sciatic-femoral block and spinal or epidural injection are widely used preemptive analgesia methods in canine stifle surgery and human knee arthroplasty. 11,[35][36][37][38][39] Both methods are seen as equivalently good in preventing perioperative pain. 36,38 We did not find any of these perioperative analgesia methods superior to another.…”
Section: Discussionmentioning
confidence: 99%
“…11,[35][36][37][38][39] Both methods are seen as equivalently good in preventing perioperative pain. 36,38 We did not find any of these perioperative analgesia methods superior to another. Previous authors reported that fentanyl rescue analgesia was administered in 13.3% and 6.7% of TPLO cases after a sciatic-femoral and spinal or epidural injection, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Sciatic/femoral block (McCally, Bukoski, Branson, Fox, & Cook, 2015;Caniglia et al, 2012;Campoy, Martin-Flores, Ludders, Erb, & Gleed, 2012;Gurney & Leece, 2014) Box 22 and Figure 11. Tissues/area desensitized: Used together, these blocks will desensitize structures of the rear limb from the distal femur through the digits.…”
Section: Other Blocks Of the Pelvic Limbsmentioning
confidence: 99%